Acute effects of air pollution on mortality: A 17-year analysis in Kuwait. (May 2019) - Achilleos, Souzana; Al-Ozairi, Ebaa; Alahmad, Barrak; Garshick, Eric; Neophytou, Andreas M.; Bouhamra, Walid; Yassin, Mohamed F.; Koutrakis, Petros
Abstract: Background: The health burden from exposure to air pollution has been studied in many parts of the world. However, there is limited research on the health effects of air quality in arid areas where sand dust is the primary particulate pollution source. Objective: Study the risk of mortality from exposure to poor air quality days in Kuwait. Methods: We conducted a time-series analysis using daily visibility as a measure of particulate pollution and non-accidental total mortality from January 2000 through December 2016. A generalized additive Poisson model was used adjusting for time trends, day of week, and temperature. Low visibility (yes/no), defined as visibility lower than the 25th percentile, was used as an indicator of poor air quality days. Dust storm events were also examined. Finally, we examined these associations after stratifying by gender, age group, and nationality (Kuwaitis/non-Kuwaitis). Results: There were 73, 748 deaths from natural causes in Kuwait during the study period. The rate ratio comparing the mortality rate on low visibility days to high visibility days was 1.01 (95% CI: 0.99–1.03). Similar estimates were observed for dust storms (1.02, 95% CI: 1.00–1.04). Higher and statistically significant estimates were observed among non-Kuwaiti men and non-Kuwaiti adolescents and adults. Conclusion: We observed a higher risk of mortality during days with poor air quality in Kuwait from 2000 through 2016. Highlights: The health effects of air quality in arid areas are not well studied. Studied the acute effect of poor air quality and dust storms on mortality in Kuwait Time-series analysis using 2000-16 daily visibility and all nonaccidental mortality People are in higher risk of dying during days with poor air quality in Kuwait. Non-Kuwaiti people especially men and adults are in higher risk.